2007
DOI: 10.1063/1.2746087
|View full text |Cite
|
Sign up to set email alerts
|

Double hysteresis loop in Cu-doped K0.5Na0.5NbO3 lead-free piezoelectric ceramics

Abstract: In this letter the authors report the observation of double hysteresis loops in Cu-doped K 0.5 Na 0.5 NbO 3 ͑KNN͒ ceramics. Unlike other ferroelectric titanates ͑e.g., BaTiO 3 ͒, aging is not required for the ceramic to exhibit the double-loop-like characteristics. Based on the symmetry-conforming principle of point defects, it is suggested that defect dipoles are formed by the acceptor dopant ions-Cu 2+ and O 2− vacancies along the polarization direction after the diffuse tetragonal-orthorhombic phase transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
139
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 7 publications
12
139
3
Order By: Relevance
“…13) and is subsequently confirmed by the EPR spectrum. 14,15 Non-switchable DCs that are aligned opposite to the spontaneous polarization (P s ) direction provide the driving force for domain backswitching after the removal of the external electric field, similar to the antiferroelectric behavior.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…13) and is subsequently confirmed by the EPR spectrum. 14,15 Non-switchable DCs that are aligned opposite to the spontaneous polarization (P s ) direction provide the driving force for domain backswitching after the removal of the external electric field, similar to the antiferroelectric behavior.…”
mentioning
confidence: 57%
“…Moreover, double P-E loops have also been reported in some acceptor-doped ferroelectrics without aging, such as in K þ -doped PbZr x Ti 1Àx O 3 (PZT) 11,12 and Cu 2þ -doped K 0.5 Na 0.5 NbO 3 (KNN) ceramics. 13 This phenomenon has been explained on the basis of the high mobility of defect dipoles, which could reorient easily after the formation of domain patterns. [11][12][13] Accordingly, aging is not required for the ceramics to exhibit double P-E loops.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the nature of the aging process can be obtained by studying the changes in the polarization -electric field (P-E) hysteresis loops which occur with aging. It is well known that after aging, a number of ferroelectric materials, such as Pb-based, 1-3 BaTiO 3 /(Ba, Sr)TiO 3, 4, 5 KNbO 3 -based, 6,7 and Bi-based 8,9 ferroelectrics, exhibit similar constricted P-E loops, regardless of their crystal structure and of their ionic species. The striking similarity of the aging effect in different ferroelectric perovskites was believed to originate from a general symmetry-conforming tendency of point defects, as stipulated by the symmetryconforming short-range ordering (SC-SRO) principle.…”
mentioning
confidence: 99%
“…The prominent studies of Ren group further show that the microscopic origin of the volume effect arises from a symmetry conforming short-range ordering (SC-SRO) principle, which provides the driving force for the migration of OVs. [8][9][10]16,17 As we all know, the relaxation of OVs is a thermally and electrically activated process, which is an important factor affecting the aging behavior. Many studies have reported the variations of P-E loops and electrostrain with temperature and frequency.…”
Section: Introductionmentioning
confidence: 99%